Transport Factors Affecting the Outcome of Referred Neonates Admitted in A Tertiary Care Hospital (Bangladesh Journal of Child Health, 2018)
Background: Adequate neonatal transport is a key component of care of the sick newborns who require referral to tertiary care center. Poor transportation is one of the iatrogenic factors associated with greater neonatal mortality. Neonatal transport is the greatest challenge faced today in our country. The purpose of this study was to find out characteristics of transport of referred neonates and to idention the factors that contribute to mortality.Methodology: This cross sectional study was conducted in Dhaka Shishu (Children) Hospital from June 2013 to November 2013. Both term and preterm neonates who were referred within first seven days of life were included and those with gross congenital abnormalities and left against medical advice were excluded from the study. After enrollment, data were collected using a structured questionnaire including birth details, interventions before transportation, reasons for referral, and details of transportation. Outcome & duration of hospital stay were also recorded. Neonates who were expired considered as group I and who were survived considered as group II. The study variables were analyzed for their association with immediate outcome by applying chi square test and t test. P value